Elucidating the Critical Role of Ruthenium Single Atom Sites in Water Dissociation and Dehydrogenation Behaviors for Robust Hydrazine Oxidation‐Boosted Alkaline Hydrogen Evolution. (5th January 2022) - Li, Jiachen; Li, Yang; Wang, Jiaao; Zhang, Chi; Ma, Huijun; Zhu, Chenhui; Fan, Daidi; Guo, Zhaoqi; Xu, Ming; Wang, Yaoyu; Ma, Haixia
Abstract: Hydrazine oxidation (HzOR)‐assisted overall water splitting (OWS) provides a unique approach to energy‐efficient hydrogen production (HER). However, there are still major challenges in the design of bifunctional catalysts and gain deep insight into the mechanism of both water dissociation and dehydrogenation kinetics triggered by the same active species during HzOR‐assisted OWS. Here, ruthenium single atoms (Ru SAs) anchored onto sulphur‐vacancies of tungsten disulphide (WS2 ) are prepared by a sulfidation and facile galvanostatic deposition strategy. The WS2 /Ru SAs act as a bifunctional catalyst and outperforms commercial platinum (Pt) catalysts for both HzOR and HER. Ultralow potentials of −74 and −32.1 mV at 10 mA cm −2 are achieved for HzOR and HER, respectively. Two‐electrode electrolyzer using WS2 /Ru SAs as both anode and cathode reaches 10 mA cm −2 with cell voltage of only 15.4 mV, which is far below that of most electrocatalysts including commercial Pt. Density functional theory calculations unravel the critical role of Ru SAs in WS2, where the sluggish dissociation of water in HER can be promoted on Ru sites, and the sulfur sites of WS2 exhibit a more thermoneutral behavior for hydrogen intermediate adsorption. Moreover, Ru sites are also active centers for stepwise hydrazine dehydrogenation during HzOR. Abstract : Single ruthenium atoms immobilized onto sulfur‐vacancies of tungsten disulfide are developed as bifunctional electrocatalysts for alkaline hydrogen evolution reaction (HER) and hydrazine oxidation reaction (HzOR). Two‐electrode HzOR‐assisted HER exhibits ultralow cell voltage of 15.4 mV at 10 mA cm −2 . An in‐depth mechanism study unravels the critical role of ruthenium sites as bifunctional active centers in improving HER and HzOR.